Justice League Dark [videorecording (Blu-Ray)] - DeMatteis, J. M.; Dawson, Rosario; Luddington, Camilla, 1983-; O'Connell, Jerry, 1974-; O'Mara, Jason (Warner Bros. Home Entertainment, 2017)
When the Justice League comes upon a supernatural force against which even their powers seem useless, Batman assembles a second geague of mystic heroes - the likes of Swamp Thing, the Demon, and Constantine - to help defeat this magical, otherworldly threat.